2015
DOI: 10.1016/j.jmb.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Mysteries of Molecular Biology: The Role of Polyamines in the Cell

Abstract: The polyamines (PAs) spermidine, spermine, putrescine and cadaverine are an essential class of metabolites found throughout all kingdoms of life. In this comprehensive review, we discuss their metabolism, their various intracellular functions and their unusual and conserved regulatory features. These include the regulation of translation via upstream open reading frames, the over-reading of stop codons via ribosomal frameshifting, the existence of an antizyme and an antizyme inhibitor, ubiquitin-independent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
553
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(568 citation statements)
references
References 228 publications
(228 reference statements)
10
553
0
5
Order By: Relevance
“…Like the archetypal trace amines, polyamines are found in all species (Miller-Fleming et al, 2015). They are traditionally viewed as consisting of cadaverine, putrescine, spermidine, and spermine.…”
Section: F Polyaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the archetypal trace amines, polyamines are found in all species (Miller-Fleming et al, 2015). They are traditionally viewed as consisting of cadaverine, putrescine, spermidine, and spermine.…”
Section: F Polyaminesmentioning
confidence: 99%
“…They are traditionally viewed as consisting of cadaverine, putrescine, spermidine, and spermine. Polyamine metabolism is complex, not least because of their ability to interconvert, and this has been detailed fully in numerous review articles (Miller-Fleming et al, 2015;Pegg, 2016). Putrescine is primarily derived from L-ornithine by the action of ornithine decarboxylase (EC 4.1.1.17; Table 1).…”
Section: F Polyaminesmentioning
confidence: 99%
“…In a recent review it was suggested that a group of genes that increase their translation in the presence of PAs, so called "PA modulon" [19] The beneficial effect of putrescine (PUT) pre-treatment, added to the hydroponic solution, against PEG-induced osmotic stress has been demonstrated earlier in wheat and maize plants [11]. The results demonstrated that fine tuning in the PA pool is important for PA signalling, which influences the hormonal balance required.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, beside arising from direct interventions of the main enzymatic and scaffolding activities of Tgase2, they might depend on the expression of mutant forms of Tgase with altered sensitivity to effectors (Lai and Greenberg 2013) or through the modification of intracellular proteins that trigger differential responses as in the case of the control of NFκB activity by polymerization of IkB (Mann et al 2006). On the other side, the opposing effects of Tgase on cell functions might relate also to cellular "receptivity", e.g., through the modulation of cellular metabolites like polyamines which are known to influence cellular responses (notably proliferation) (Miller-Fleming et al 2015), as well as to accumulate inside the cells as protein-polyamine adducts (Folk et al 1980;Haddox and Russell 1981;Lentini et al 2004). In addition, in several cell types overexpression of Tgase2 and alternatively its suppression alter features of the cell cycle and these effects are apparently triggered by both native and transamidation inactive mutants as reviewed by Nurminskaya and Belkin (2012) suggesting that the likelihood that these effects are linked directly to protein-protein interaction or alternatively to G-protein activity rather than to the transamidation required to modify the activity of transcription factors like NFκB or Sp1 or the signaling through the TGFβ pathway.…”
Section: The Physiology: Integrated Responses Of Cells and Tissuesmentioning
confidence: 99%